ANALISIS KEMAMPUAN REPRESENTASI SISWA DALAM MENYELESAIKAN SOAL MATEMATIS BERBASIS ETNOMATEMATIKA - Rina Nur Janna; Eric Dwi Putra; Dwi Noviani Sulisawati (Universitas Insan Budi Utomo, 2024)
This research aims to analyze the representational abilities of junior high school students in solving ethnomathematics-based mathematical problems. The newest thing is to see the representation of junior high school students when working on ethnomathematics-based mathematical problems, namely the engklek game. The type of research carried out in this research is qualitative research. Data collection methods use tests and interviews. The subjects in this research were MTs 1 Putri Annuqayah students whose address is Jalan Komplek PP Annuqayah Guluk-guluk Sumenep class IX Amazing, 2 students with high mathematical abilities and 2 students with low mathematical abilities. The results of the research show that students with high mathematical abilities are able to fulfill all indicators of representational abilities, namely verbal, visual and symbolic representational abilities, while students with low mathematical abilities are only able to fulfill one indicator of representational abilities, namely symbolic representational abilities.